ADHD Symptoms, Entrepreneurial Orientation (EO), and Firm Performance - Perez-Luno, Ana (My University, 2021)
Recently, scholars have started to investigate the relationship between ADHD (Attention Deficit Hyperactivity Disorder) symptoms and entrepreneurship, finding that ADHD symptoms positively impact entrepreneurial intention and action. However, the performance implications of ADHD symptoms are still unknown. Using two samples of entrepreneurs from the United States and Spain, we find evidence that impulsive and hyperactive symptoms of ADHD are largely conducive to firm performance through entrepreneurial orientation (EO) while in- attention symptoms are not. This suggests that the performance advantages of entrepreneurs ADHD symptoms can be derived from greater focus on innovation, proactiveness, and risk- taking. We discuss the implications of our findings for the entrepreneurship literature.
FRONTIERS OF ENTREPRENEURSHIP RESEARCH
Keywords: ADHD, entrepreneurial orientation, venture performance, personality, mental health; Inclusive Society; Entrepreneurship, innovation; Human Resource Management